Case Report: Reversible neurological involvement associated with Chlamydia psittaci infection: clinical, cerebrospinal fluid and neuroimaging features of three fully documented cases - Hao Zhang; Jia Zhou; Yong Chen; Xiuyan Wang; Xiaoping Luo; Guilan Yang; Zhenzhen Gui; Shuni Wang; Yanan Zhang; Juan Chen (Frontiers in Medicine, 2026)
Background Chlamydia psittaci infection presents mainly as severe pneumonia, but a subset of patients develop neurological symptoms. Previous reports are largely single cases and frequently lack cerebrospinal fluid (CSF) data, opening pressure and follow-up imaging, which makes the mechanism of neurological involvement difficult to determine. Methods We retrospectively analysed three patients with C. psittaci infection confirmed by metagenomic next-generation sequencing (mNGS), all of whom developed neurological manifestations and had complete clinical, CSF, neuroimaging and follow-up data. Exposure history, neurological phenotype, laboratory and CSF parameters, opening pressure, treatment and outcome were collected. Potential explanations for neurological involvement were interpreted in the context of the clinical findings and published literature. Results All three patients (two men and one woman; aged 50–72 years) reported pigeon or poultry exposure. Two presented with encephalopathy/delirium and one with headache. Opening pressures were 160, 230 and 90 mmH₂O; none exceeded 250 mmH₂O. CSF white-cell counts were 0–2/mm³, with mild protein elevation in one patient, and the CSF pathogen tests performed were negative. This mismatch between neurological manifestations and routine CSF findings met the study's operational description of CSF–clinical dissociation. Two patients had reversible splenial lesions consistent with cytotoxic lesions of the corpus callosum (CLOCCs). Hypoalbuminemia was present in all three patients, whereas hyponatremia and coagulation abnormalities occurred in selected cases. Neurological symptoms resolved within 4–7 days after pathogen-directed therapy, and all patients recovered completely during follow-up. Conclusions In these three fully documented cases, C. psittaci-associated neurological involvement was short-lived and reversible. The clinical–CSF mismatch was consistent with the hypothesis that unmeasured indirect processes may have contributed, but it did not establish a mechanism or exclude low-burden direct CNS infection. Reversible splenial lesions consistent with CLOCCs were a notable imaging finding. Co-detected organisms and systemic complications limited pathogen-specific causal attribution. Clinical improvement was temporally associated with pathogen-directed therapy.